PENGARUH SOSIALISASI TENTANG BERDIRINYA KOPERASI DESA MERAH PUTIH TERHADAP MANFAATNYA BAGI MASYARAKAT PETANI DI DESA TANJUNG REJO DUSUN I KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Rahmi Sari, Joni Rianto Siregar, Irhamna Mandily Lubis (JURNAL BIMA, 2026)
Village cooperatives play an important role in improving the welfare of farming communities, but are often less than optimal due to a lack of understanding of their functions and benefits. This study aims to analyze the influence of socialization regarding the establishment of the Merah Putih Village Cooperative on the benefits received by farming communities in Tanjung Rejo Village, Dusun I, Percut Sei Tuan District. The community service methods used were socialization, discussion, and structured interviews with 30 farmer respondents who are members of the cooperative. The results of the study indicate that the socialization carried out had a significant positive influence on farmers' understanding of the function of cooperatives, thereby increasing the benefits received, including access to affordable capital, a supply of quality seeds and fertilizers, and better marketing of crops. Before the socialization, only 23% of farmers understood the benefits of cooperatives, while after the socialization, this increased to 87%. The conclusion of this study is that effective socialization can enhance the role of cooperatives as institutions for economic empowerment of farming communities.